2017
DOI: 10.3732/apps.1600124
|View full text |Cite
|
Sign up to set email alerts
|

Applying pollen DNA metabarcoding to the study of plant–pollinator interactions

Abstract: Premise of the study:To study pollination networks in a changing environment, we need accurate, high-throughput methods. Previous studies have shown that more highly resolved networks can be constructed by studying pollen loads taken from bees, relative to field observations. DNA metabarcoding potentially allows for faster and finer-scale taxonomic resolution of pollen compared to traditional approaches (e.g., light microscopy), but has not been applied to pollination networks.Methods:We sampled pollen from 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
155
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(168 citation statements)
references
References 47 publications
4
155
0
Order By: Relevance
“…First and perhaps foremost, pollen metabarcoding data currently cannot be treated as if they are quantitative, given the lack of consistent relationship between sequence counts and pollen grain proportions. This does not mean that quantitative results can never be generated by metabarcoding; for example, samples which are assessed for the presence/absence of plant species can be aggregated to generate proportions of samples with particular plant species present, which can be useful for pollination network studies among other study types (Bell, Fowler, et al., ). Second, it is standard procedure to use negative controls for PCR‐based methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First and perhaps foremost, pollen metabarcoding data currently cannot be treated as if they are quantitative, given the lack of consistent relationship between sequence counts and pollen grain proportions. This does not mean that quantitative results can never be generated by metabarcoding; for example, samples which are assessed for the presence/absence of plant species can be aggregated to generate proportions of samples with particular plant species present, which can be useful for pollination network studies among other study types (Bell, Fowler, et al., ). Second, it is standard procedure to use negative controls for PCR‐based methods.…”
Section: Discussionmentioning
confidence: 99%
“…Small-scale studies have demonstrated proof of concept, and the field has advanced significantly over the past few years. Pollen DNA (meta)barcoding has been applied to airborne allergen monitoring (Kraaijeveld et al, 2015), plant-pollinator interactions (Bell, Fowler et al, 2017;Galimberti et al, 2014;Keller et al, 2015;Richardson, Lin, Quijia, et al, 2015a;Richardson, Lin, Sponsler, et al, 2015Sickel et al, 2015 and quality control of honey (Hawkins et al, 2015;Valentini, Miquel, & Taberlet, 2010;de Vere et al, 2017). Its potential has also been recognized for examining changes in plant communities over time (Suyama et al 1996;Parducci, Suyama, Lascoux, & Bennett, 2005, Parducci et al, 2017, and in forensics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes extracting DNA from sources such as bulk samples or insect soups (Arribas, Andújar, Hopkins, Shepherd, & Vogler, 2016;Elbrecht et al, 2016;Hajibabaei, Shokralla, Zhou, Singer, & Baird, 2011;Yu et al, 2012), empty leaf mines (Derocles, Evans, Nichols, Evans, & Lunt, 2015), spider webs (Blake, McKeown, Bushell, & Shaw, 2016;Xu, Yen, Bowman, & Turner, 2015), pitcher plant fluid (Bittleston, Baker, Strominger, Pringle, & Pierce, 2015), environmental samples like soil and water (environmental DNA [eDNA]) (Taberlet, Coissac, Hajibabaei, & Rieseberg, 2012;Thomsen et al, 2012;Thomsen & Willerslev, 2015;Zinger et al, 2018), host plant and predatory diet identification from insect DNA extracts (Jurado-Rivera, Vogler, Reid, Petitpierre, & Gómez-Zurita, 2009;Paula et al, 2016), and predator scat from bats (Bohmann et al, 2011;Vesterinen, Lilley, Laine, & Wahlberg, 2013). Recently, also DNA from pollen attached to insects has been used for retrieving information on plant-pollinator interactions (Bell et al, 2017;Pornon et al, 2016). Many of such recent studies rely on DNA metabarcoding-high-throughput sequencing of PCR amplicons using generic primers (Taberlet, Bonin, Zinger, & Coissac, 2018;Taberlet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rare species are prone to being overlooked in subsampling and microscopic examination. Alternatively, molecular identifications such as metabarcoding have seen increasing applications in bulk pollen characterizations (Bell et al, 2016(Bell et al, , 2017Cornman, Otto, Iwanowicz, & Pettis, 2015;Danner, Molitor, Schiele, Härtel, & Steffan-Dewenter, 2016;Galimberti et al, 2014;Kamo et al, 2018;Keller et al, 2015;Pornon et al, 2016;Richardson et al, 2015). Metabarcoding employs high-throughput sequencing (HTS) in analysing pooled amplicons obtained from mixed taxa (Cristescu, 2014;Ji et al, 2013).…”
mentioning
confidence: 99%